Strategies Endogenesde Gestion des Ressources Naturelles : Cas des Forets Sacrees de la Commune de Tori-Bossito au Benin (Afrique de l’ouest) - Oscar, Hountondji Müller; Césaire, Ajavon Ayi Yves; Brice, Tente A. H.; Brice, Sinsin A. (European Scientific Journal, ESJ, 2019)
Sacred forests constitute not only botanical reservoirs in the same way as the protected areas of the State, but also true means of communication, protection, prevention and conjuration of certain misfortunes. The present study is a contribution to a better knowledge of the diversity of sacred forests and the endogenous strategies implemented for their conservation in the Municipality of Tori-Bossito. The methodological approach used was based on socio-anthropological surveys of dignitaries, curators and traditional healers in the localities of the Commune, which are home to these sacred forests. In addition, the geographical coordinates of these sacred forests have been geo-referenced using a GPS. The results obtained reveal 51 sacred forests distributed in the six districts. They cover a total area of 38.55 ha and are divided into 3 categories, namely: the fetish forests (28 in number), the secret societies forests (21 in number) and the cemetery forests (02 in number). Ten endogenous management strategies for these sacred forests have been identified. These strategies are complementary and effectively contribute to the conservation of biodiversity in the Commune. Les forêts sacrées malgré leur rôle très important dans la vie socioéconomique d’une nation, subissent une nette régression due aux actions anthropiques. La présente recherche est une contribution à une meilleure connaissance de la diversité des forêts sacrées et des stratégies endogènes mises en œuvre pour leur conservation dans la Commune de Tori-Bossito. La démarche méthodologique utilisée s’est articulée autour des enquêtes socio anthropologiques auprès des dignitaires, des conservateurs et des tradithérapeutes dans les localités de la Commune abritant ces forêts sacrées. Par ailleurs, ces forêts sacrées ont été géo référencées au moyen d’un GPS Garmin 60. Les résultats obtenus révèlent 51 forêts sacrées réparties dans les six arrondissements de la commune de Tori-Bossito. Elles couvrent une superficie total de 38,55 ha et subdivisées en 3 catégories à savoir : les forêts fétiches (au nombre de 28), les forêts de sociétés secrètes (au nombre de 21) et les forêts cimetières (au nombre de 02). Dix (10) stratégies endogènes de gestion de ces forêts sacrées dont la sacralisation ; les interdits ; la délimitation ; l’association des divinités ;… ont été mises en évidences. Ces stratégies sont complémentaires et participent effectivement à la conservation de la biodiversité dans la Commune.